Prevalence, trend and disparities of palliative care utilization among hospitalized metastatic breast cancer patients who received critical care therapies - Ying Chen; Shuchen Lin; Yihui Zhu; Rui Xu; Xiaohong Lan; Fang Xiang; Xiang Li; Ye Zhang; Shudong Chen; Hao Yu; Dongni Wu; Juxiang Zang; et al. (Breast, 2020)
Background: Early integration of palliative care (PC) for patients with advanced cancer has been recommended to improve quality of care. This study aims to describe prevalence, temporal trend and predictors of PC use in metastatic breast cancer (mBCa) patients receiving critical care therapies (CCT; included invasive mechanic ventilation, percutaneous endoscopic gastrostomy tube, total parenteral nutrition, tracheostomy and dialysis). Methods: The National Inpatient Sample was queried for mBCa patients receiving CCT between 2005 and 2014. Annual percent changes (APC) were calculated for PC prevalence in the overall cohort and subgroups. Multivariable logistic analysis was used to explore predictors of PC use. Results: Of 5833 mBCa patients receiving CCT, 880 (15.09%) received PC. Rate of PC use increased significantly from 2.53% in 2005 to 25.96% in 2014 (APC: 35.75%; p < 0.0001). Higher increase in PC use was observed in South (from 0.65% to 27.11%; APC: 59.42%; p < 0.0001), medium bedsize hospitals (from 3.75% to 26.05%; APC: 38.16%; p = 0.0006) and urban teaching hospitals (from 4.13% to 29.86%; APC: 37.33%; p = 0.0005). Multivariable analysis revealed that year interval, urban teaching hospitals, and invasive mechanical ventilation were associated with increased PC use, while primary diagnosis of gastrointestinal disorders, fractures, metastatic sites from lymph nodes and tracheostomy were associated with lower PC use. Conclusions: PC use in mBCa patients receiving CCT increases significantly over the period. However, it still remains low. Efforts to illustrate disparities in PC use are needed to improve quality of care for mBCa patients receiving CCT, especially for those hospitalized in rural and nonteaching hospitals.